A modified stress model to predict the ultimate bending strength of solid timber beams using plastic approach - Khin, Maung Zaw; Mohamed, Zainai; Saleh, Abd. Latif; Abu Bakar, Suhaimi (Faculty of Civil Engineering, UTM, 2005)
A modified stress model based on the principle of plasticity to predict the ultimate bending strength of solid timber beams was developed. The model is capable to predict the actual bending strength of timber beams better than the existing stress models. The two main controlling parameters of the model are the ultimate tensile and compressive strengths of the beam material. The proposed model was verified through a series of laboratory experiments using a local hardwood timber, Dark Red Meranti. A number of specimens consisting of 12 beams. 10 tension specimens and 15 compression specimens were tested. The ultimate bending moment from test results were compared against the proposed and existing stress models. A significant non-linear relationship exists between load and deformation of timber in both bending and compression, but the stress-strain relationship is linear in tension. The strain is distributed linearly across the beam section and the neutral axis tends to shift towards the tensional side when the beam is loaded beyond the proportional limit. Although the tensile strength of the timber is larger than its compressive strength, the modulus of elasticity in tension and compression is approximately the same.